2005
DOI: 10.1116/1.1856467
|View full text |Cite
|
Sign up to set email alerts
|

Effects of amine- and pyridine-terminated molecular nanolayers on adhesion at Cu–SiO2 interfaces

Abstract: Articles you may be interested inEffect of surface hydrophilicity on the nanofretting behavior of Si(100) in atmosphere and vacuum Recent work has shown that molecular nanolayers ͑MNLs͒ are attractive candidates for isolating and enhancing adhesion of Cu/ SiO 2 interfaces for sub 100 nm integrated circuits. Here, we report the effects of solution concentration and SiO 2 surface treatment on the adhesion of Cu/ SiO 2 interfaces treated with organosilane MNLs with two different nitrogen-containing termini. MNLs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 26 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…The Ni films remain adherent at processing temperatures as high as ∼400 °C , indicating that the underlying SAM remains intact, in contrast to the poor thermal stability of SAMs in air but comparable to their thermal stability in a vacuum . In related work, ligand SAMs alone have been shown to function as effective adhesion promoters , and diffusion barriers for Cu metal, as demonstrated by the fabrication of functional MOS capacitors using ligand SAM templates. At Nagoya University, Koumoto and co-workers , have pioneered the use of both Pd−Sn and PD1-type Sn-free catalysts for patterned EL deposition of oxide features, such as ZnO and In 2 O 3 , useful for optoelectronics applications.…”
Section: Process Extensions and Challengesmentioning
confidence: 99%
“…The Ni films remain adherent at processing temperatures as high as ∼400 °C , indicating that the underlying SAM remains intact, in contrast to the poor thermal stability of SAMs in air but comparable to their thermal stability in a vacuum . In related work, ligand SAMs alone have been shown to function as effective adhesion promoters , and diffusion barriers for Cu metal, as demonstrated by the fabrication of functional MOS capacitors using ligand SAM templates. At Nagoya University, Koumoto and co-workers , have pioneered the use of both Pd−Sn and PD1-type Sn-free catalysts for patterned EL deposition of oxide features, such as ZnO and In 2 O 3 , useful for optoelectronics applications.…”
Section: Process Extensions and Challengesmentioning
confidence: 99%
“…For an application such as a diffusion barrier, the near-zero thickness of the molecular layers will maximize the fraction of the total via volume available for low-resistivity Cu filling. The effect of solution concentration of organosilane MNLs with two different N-containing termini (TMSEP and p-amino-phenyltrimethoxy-silane (APhTMS) ) on the Cu/SiO 2 interface adhesion was investigated by Ganesan et al [252]. Molecular nanolayers with short tail lengths (phenyl-trimethoxy-silane) or aliphatic terminal groups (n-propyl-trimethoxy-silane) are ineffective in hindering Cu diffusion, indicating that the molecular length and chemical configuration are key factors determining the efficacy of MNLs as barriers [246].…”
Section: Self-assembled Molecular Nanolayers and Polymer-based Barriersmentioning
confidence: 99%
“…In one of the first studies employing MNLs as a barrier layer against Cu diffusion, Krishnamoorthy et al [246] showed that Cu/SiO 2 /Si(001) MOS capacitors with integrated 3-[2-(trimethoxysilyl)ethyl]pyridine (TMSEP) MNL at the metal/dielectric interface and annealed at 200 °C in a 2 MV/cm electrical field are characterized by more than 10 4 times lower leakage current and a four times higher time to failure when compared to samples without MNLs. Since the Cu/MNL interface is the weakest one, MNLs with termini that bond strongly with Cu are expected to show improvements in interface adhesion [252]. According to Ramanath et al [247], integrating a ∼0.7 nm thick 3-mercapto-propyl-trimethoxy-silane (MPrTMS) MNL between Cu and SiO 2 results in enhanced interface adhesion (three times higher interface debond energy) and inhibition of Cu diffusion at the Cu/SiO 2 interface (four times higher time to failure), which is due to a strong chemical interaction between Cu and the sulfurcontaining MNL termini [247].…”
Section: Self-assembled Molecular Nanolayers and Polymer-based Barriersmentioning
confidence: 99%
“…1 and 2, we can conclude that the optimized set of ELD experimental conditions leads to the maximum Cu/Si ratio on the APTS-functionalized surface (data not shown). 3 a and b. Ganesan et al [15] reported that the interfacial debonding energy of the PVD Cu/NH 2 surface is ca. Cu shows a high mobility on the SiO 2 surface due to the weak interaction between Cu and O atoms, attributed to van der Waals forces acting at the Cu-SiO 2 interface [14].…”
Section: Eld Cu Nucleation and Growth On Clean Sio 2 And Apts-functiomentioning
confidence: 99%